Mathematics teachers' perceptions of eBook use in mathematics lesson: a preliminary study - Abd Jalal, Azlin; Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The utilization and effectiveness of eBook integration in mathematics teaching and learning depends largely on the teachers as they are the change agents in the classrooms. Therefore, we need to understand the teachers’ perceptions and beliefs that underlie their decision making process. The eBook, a mini laptop complete with digitized textbook softwares, were introduced in Terengganu in 2009, in line with the concept of 1 student : 1 laptop. This study focuses on assessing the level of factors that might influence the acceptance of eBook in the teaching and learning of mathematics, namely the perceived usefulness, the perceived ease of use, the attitude and behavioural intention. Data were collected from 34 mathematics teachers in primary schools in Terengganu using a survey questionnaire. The findings in this study concluded that the level of perceived usefulness and the perceived ease of use of the eBook among mathematics teachers are moderate. Consequently, the attitude towards using of the eBook and the behavioural intention to use the eBook are also found to be moderate as well.